Conversion of Human Umbilical Cord Mesenchymal Stem Cells in Wharton’s Jelly to Dopamine Neurons Mediated by the Lmx1a and Neurturin In Vitro: Potential Therapeutic Application for Parkinson’s Disease in a Rhesus Monkey Model - Yan, Min (Public Library of Science, 2013)
hUC-MSCs hold great promise in vitro neuronal differentiation and therapy for neurodegenerative disorders including Parkinson’s disease. Recent studies provided that Lmx1α play an important role in the midbrain dopamine cells differentiation. Neurturin is desired candidate gene for providing a neuroprotective to DA neurons. In this study, we investigated a novel neuronal differentiation strategy in vitro with Lmx1α and NTN. We transferred these two genes to hUC-MSCs by recombinant adenovirus combined with Lmx1α regulatory factor and other inductor to improve the efficiency of inducing. Then those induced cells were implanted into the striatum and substantia nigra of MPTP lesioned hemi-parkinsonian rhesus monkeys. Monkeys were monitored by using behavioral test for six months after implantation. The result showed that cells isolated from the umbilical cord were negative for CD45, CD34 and HLA-DR, but were positive for CD44, CD49d, CD29. After those cells were infected with recombinant adenovirus, RT-PCR result shows that both Lmx1α and NTN genes were transcribed in hUC-MSCs. We also observed that the exogenous were highly expressed in hUC-MSCs from immunofluorescence and western blot. Experiments in vitro have proved that secretion NTN could maintain the survival of rat fetal midbrain dopaminergic neurons. After hUC-MSCs were induced with endogenous and exogenous factors, the mature neurons specific gene TH, Pitx3 was transcripted and the neurons specific protein TH, β-tubulinIII, NSE, Nestin, MAP-2 was expressed in those differentiated cells. In addition, the PD monkeys, transplanted with the induced cells demonstrated the animals’ symptoms amelioration by the behavioral measures. Further more, pathological and immunohistochemistry data showed that there were neuronal-like cells survived in the right brain of those PD monkeys, which may play a role as dopaminergic neurons. The findings from this study may help us to better understand the inside mechanisms of PD pathogenesis and may also help developing effective therapy for Parkinson’s disease.